Epidemiological Survey of Traumatic Eye Injury in A Southwestern Nigeria Tertiary Hospital - Olusola J Omotoye, Iyiade A Ajayi, Kayode O Ajite (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate the prevalence, pattern and causes of ocular trauma in Nigerians. Material and Methods: This is a prospective hospital based study over a 15 month period. Eighty five patients of all ages presenting with acute eye injuries to one or both eyes were included. Patients who had healed ocular trauma or had been given surgical treatment for trauma elsewhere were excluded from this study. All patients with eye trauma seen within this period were included in the study, relevant data was recorded with a structured questionnaire and analysed with SPSS version 13. Results: There were 91 eyes of 85 patients which constituted about 4% of all new patients seen over the study period. Male to female ratio was 2:1 with age ranged between 4 years and 78 years (mean = 31.7 ± 19.7 years). More than half of the patients (53.1%) were in the working age group of 20–60 years. Twothird presented to the clinic after 24 hours of injury with about 43.5% presenting with blindness in the affected eye. Of the patients, 69.4% had applied various forms of medication before presentation. Closed globe injuries accounted for 87% of all injuries with occupational and leisure activities constituting a greater proportion of the activity at the time of injury. Majority (98.8%) of the patients were not wearing any protective device at the time of injury. Conclusion: Ocular injuries affected mostly the economically active age group. Most injuries were either occupational related or related to play or assaults. Many patients engaged in some form of self-care before presentation. Key words: Ocular trauma, open globe injury, blindness.